PENERAPAN METODE SMALL GROUP WORK TERHADAP KEMAMPUAN MENYUSUN PARAGRAF EKSPOSISI PADA SISWA KELAS VII SMP NEGERI 1 LAWE ALAS TAHUN PEMBELAJARAN 2019/2020 - Rekaza Akbar (Universitas Muhammadiyah Tapanuli Selatan, 2019)
The purpose of this study was to determine the effect of the application of matedo small group work on the ability to compile an exposition paragraph in class VII students at SMP Negeri 1 Alas 2019/2020 academic year. The research population was 102 students, the research sample was 21 students taken with systematic sampling. The experimental method with quantitative descriptive analysis, by doing a simple regression analysis and F test. The data obtained is the average initial test (Pree test) of students by 5.5 with a standard deviation (SDx) of 6.34, with graduation criteria a total of 1 8 students did not graduate and 3 students graduated. After the learning process is carried out using the small group work method the average score of students' final test (Post test) is 74.76 and the standard deviation (SDy) is 6.22 with a graduation criteria of 21 students graduating. Calculations using the F test were found to be a F value of 6.65. After analyzing it was found that the calculated value of 6.65> 4.35 at a significance of 0.05 then learning using the small group work method affected the ability of students to compose an exposition paragraph so that the hypothesis was accepted. The conclusion of the research is that the application of the small group work method has an effect on the ability to deal with the exposition paragraphs of grade VII students at SMP Negeri 1 Lawe Alas in the academic year 2019/2020.Keywords: matedo small group work, Exposition Paragraph